A rare indication for video‐assisted thoracoscopic surgery: headscarf needle aspiration. (8th July 2013) - Ghanim, Bahil; Ankersmit, Hendrik Jan; Prosch, Helmut; Klikovits, Thomas; Marta, Gabriel; Klepetko, Walter; Lang, Gyorgy
Abstract Headscarf needle aspiration is a rare event, especially in Middle and Western European countries. Here, we report the case of a 37‐year‐old Austrian woman of Turkish origin who accidentally aspirated a turban pin. Repeated bronchoscopy was not successful in removing the aspirated foreign body, which extended past the right middle lobe to the interlobar fissure. The needle was finally removed by video‐assisted thoracoscopic surgery.